HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR PASTRY AND ART MAHASISWA PRODI PKK UNIVERSITAS NEGERI PADANG - Saputri, Marisa Ayu; Elida, Elida; Fridayati, Lucy (Journal of Home Economics and Tourism, 2016)
This study aims to describe the motivation and learning outcomes andÂ  analyze the relationship between motivation with learning outcomes in subjects Pastry and Art Student of PKK UNP. The study was correlational, with a population of 79 people and a sample of 45 people who were taken by random sampling technique. Data Sources students who have taken courses Pastry and Art. Data collection techniques by using a questionnaire were designed based on Likert scale. The results of this study portrait (1) student motivation Pastry and Art student of PKK UNP overall 45 (100%) included in the category enough (2) learning outcomes Pastry and Art students of PKK UNP included in both categories, with the percentage of 21 persons ( 47%). (3) There is a positive and significant relationship between motivation and learning outcomes of students in the subject of Pastry and Art with the value of the correlation coefficient of 0.221 which is in the range 0.25 to 0.5, with significant value 0,045 because of significant value <0.05. Â Keywords: Motivation, Students, Pastry and Art